#### Answer

$x=3$
conditional equation

#### Work Step by Step

$\frac{3}{x-3}=\frac{x}{x-3}+3$
$\frac{3}{x-3}=\frac{x}{x-3}+3(\frac{x-3}{x-3})$
$\frac{3}{x-3}=\frac{x+3(x-3)}{x-3}$
$3=x+3(x-3)$
$3=x+3x-9$
$3=4x-9$
$4x=12$
$x=3$

Published by
Pearson

ISBN 10:
0-32178-228-3

ISBN 13:
978-0-32178-228-1

$x=3$
conditional equation

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.